1899 N.Y. Laws 1341, ch. 603, § 1 - (:unkn) unknown (General Publisher, 1899)
Prohibited the selling or giving to a minor under the age of eighteen any pistol or other firearm. Also prohibited the selling or giving away any air-gun or spring-gun to minors under the age of twelve. Violators guilty of a misdemeanor.
--
Keywords: TRANSFER - MINORS